2018
DOI: 10.7567/jjap.57.101601
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study on heat conduction in poly(3,4-ethylenedioxythiophene)

Abstract: The poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) composite has been gaining attention as a potential organic thermoelectric material owing to its superior electrical property and low thermal conductivity. Several experiments have recently demonstrated that introduction of high-boiling-point solvents increases optimal charge carrier concentration and leads to high crystallinity, resulting in noticeable improvement of thermoelectric performance. Therefore, much attention has been paid to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…The analysis of the morphology of the polymer films shows that the anisotropy of thermal conductivity originates from the chain orientations. Other molecular dynamics study performed by Maeno et al [131] has also found a large anisotropy of thermal conductivity in PEDOT. Their simulation results have shown that a single PEDOT chain with a length of 2-35 nm has high thermal conductivity ranging 4-27 W m −1 K −1 along the chain direction, which is higher than the thermal conductivity of polymers with randomly twisted and entangled chains.…”
Section: Alignment Of Chain Orientationsmentioning
confidence: 68%
“…The analysis of the morphology of the polymer films shows that the anisotropy of thermal conductivity originates from the chain orientations. Other molecular dynamics study performed by Maeno et al [131] has also found a large anisotropy of thermal conductivity in PEDOT. Their simulation results have shown that a single PEDOT chain with a length of 2-35 nm has high thermal conductivity ranging 4-27 W m −1 K −1 along the chain direction, which is higher than the thermal conductivity of polymers with randomly twisted and entangled chains.…”
Section: Alignment Of Chain Orientationsmentioning
confidence: 68%
“…21,50 The along-chain thermal conductivity (κ y ) is lower than that in previous MD results. 38,39 This discrepancy is attributed to different simulation method and force field. The equilibrium MD method is widely used to simulate the thermal transport of bulk materials.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…37 Recently, through molecular dynamics (MD) simulations, Shi et al reported the along-chain thermal conductivity values of PEDOT:Tos on the order of 10 Wm −1 K −1 . 38 Maeno et al 39 and Crnjar et al 40 investigated the alongchain thermal transport in PEDOT chains by MD simulations. Yet, the effect of dopants on thermal transport has not attained enough attention.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this prediction, κ can be reduced either by reduction in the product Cλ(λ,T)ν(λ) through phonon confinement in nanomaterials and superlattices with extremely small dimensions, or by reducing L(λ ,T) through enhancement of phonon boundary and interface scattering. In order to optimize the thermal conductivity in a given material, theoretical approaches have been developed including molecular dynamics simulations, [87] firstprinciples calculations, [88] and machine learning, data-driven methods. [89,90] Experimental measurement of phonon transport is more challenging.…”
Section: Thermal Conductivitymentioning
confidence: 99%